Analysis of Industrial Engineering Brand Awareness Improvement Using SWOT and Quantitative Strategic Planning Matrix (QSPM) - Muhammad Raodhany (Trigin Publisher, 2021)
There are many universities in Indonesia that have Industrial Engineering Departments, until 2015 the Industrial Engineering Study Program was registered in 187 universities. There were only 6 out of 100 respondents who wanted to enter the Industrial Engineering Department, University X, and as many as 54% did not understand the major– majors in the Faculty of Engineering, University X, based on the questionnaire distributed. In this study, the SWOT and QSPM strategies were carried out in order to be able to analyze how to increase the level of brand awareness in Industrial Engineering University X. The distribution of the first questionnaire was used to find out where the brand awareness was in the Industrial Engineering Department, University X with high school students as respondents. The second questionnaire was distributed to find out whether the internal or external factors contained in the Department of Industrial Engineering, University X were strengths or weaknesses. With the presence of internal and external factors, the SWOT strategy can be implemented. The SO strategy is the right thing to do by the Department of Industrial Engineering, University X based on a SWOT analysis. These strategies include: 1) socializing the achievement of JTI UX that has been accredited A and an average GPA of above 3 to prospective students. 2) increase the number of lecturers who are involved in Joint Research on S2 and S3 lecturers. 3) increase accreditation to international level. 4) increase the number of cooperation with international industry. 5) increase and expand cooperation in the fields of education, research, and community service with external parties both at the national and international levels. 6) make Industrial Engineering graduates who are in national or international industries to help fill guest lectures at the Department of Industrial Engineering, University X. Based on the analysis of the QSPM method, a highly recommended strategy is to increase accreditation to an international level.